Safe and effective exercise for overweight youth - Sothern, Melinda S. (CRC Press, 2014)
"Drawing on the recommendations of leading health and fitness organizations, this timely book develops a 20-week exercise program to assist children in achieving a healthy weight. Providing specific recommendations for intensity, duration, frequency, and modality of exercise for patients with significant obesity and chronic health issues such as hypertension, asthma, and diabetes, it covers aerobic exercise, strength training, flexibility training, motivation techniques, tracking techniques, measurements for health and fitness outcomes, and future trends in exercise research for overweight youth"--Provided by publisher.